Konstruksi Estetika Vitalisme - Fidausy, M. Anwar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
The intellectual contact of Iqbal to Western paradigm has a great influence over his mature thought. The subjective view of Moslem toward reality has led them fall mentally to a slave at the time. It is mainly due to philosophical doctrine they believe about the self-denial for the reality. Iqbal, moreover, has big desire to bring them into a better world by proposing an idea of self-awareness to reality. He argued that the essence of human life is to view the reality objectively not subjectively as they had believed before. The life is so real that we have to take a big part in reality as we are not victims of tragic imagination. Along with this assumption, Iqbal conceded a thought pattern regarding esthetics. Esthetics is a quality making every parts of life shine, putting self-vitality as dynamic center for desire, efforts, aspiration, strength, and action